Inventarisasi Tumbuhan Pionir Lahan Bekas Tambang Kapur Di Kecamatan Rengel Kabupaten Tuban Jawa Timur - Riska Andriani; Hesti Kurniahu; Sriwulan Sriwulan (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
Environmental damage included the limestone mining process would remove the topsoil layer, reduce fertility, reduce microbial diversity and eliminate the vegetation that growth above it. Naturally, pioneer plants could grow to replace lost plants. Pioneer plants can be used as a reference for land recovery because these plants could grow on damaged land because they are associated with Plant Growth Promoting Rhizobacteria (PGPR). In addition, the presence of pioneer plants could inhibit soil erosion due to its root ability to hold the soil from scouring water. This study aimed to determine the characteristics of the initial natural succession process, namely the pioneer post-limestone mining community. This research was conducted by purposive random sampling method at three mining locations, namely Banjaragung Village, 5 years after mine, Maibit Village, 8 years after mine, and Rengel Village, 7 years after mine. Samples were taken for each of the 10 plots of 1x1 m size. The results of this study obtained 5 types of plants with the highest INP, namely: Lamium barbatum, Chromolena odoratum, Tridax procumbens, Waltheria indica, and Digitaria sanguinalis. While the highest diversity index is in the Village of Maibit, Rengel Sub-District, Tuban Regency after 8 years post-mining, which is 2.54.